A Community-Based Participatory Approach to Stunting Prevention through Maternal and Child Health Education in Central Java - Wahju Dyah Laksmi Wardhani; Nong Chai; Shaumiwaty Shaumiwaty; Ton Kiat (Yayasan Adra Karima Hubbi, 2025)
Background. Stunting is a major public health problem in Indonesia, especially in Central Java, where socioeconomic gaps and limited maternal health education persist. Low nutritional knowledge among pregnant women and caregivers delays early prevention, affecting child growth. Community participation is increasingly viewed as a key strategy to strengthen health literacy. Purpose. To evaluate the effectiveness of a community-based participatory approach in improving maternal knowledge, feeding practices, and early caregiving behaviors related to stunting prevention. Method. A mixed-methods design was used, combining surveys and focus group discussions with 65 pregnant women and caregivers in three Central Java districts. The intervention involved collaborative health education led by midwives, health workers, and local women leaders. Quantitative data were analyzed descriptively and with paired t-tests; qualitative data were thematically coded. Results. Maternal health knowledge increased significantly (p < .001), and complementary feeding practices improved in line with national guidelines. Participants also reported higher confidence in monitoring growth and understanding nutrition. Qualitative data showed that collective learning strengthened social support for early stunting prevention. Conclusion. Participatory education builds community ownership, supports behavioral change, and improves the sustainability of maternal and child health programs. Scaling this model may contribute to national efforts to reduce stunting and enhance child well-being.